Demoeconomics: the interconnection of water resources and demoethical values - Zhanbayev, R.A.; Maksimov, D.G.; Sagintayeva, S.S.; Madenova, A.E. (BUKETOV BUSINESS REVIEW, 2024)
Object: Application of conceptual analysis within the framework of the concept of demoeconomics to study the relationship of water resources with the values of “Demoethics” as a tool for society sustainable development. Methods: This work uses a systematic approach to research, which includes a wide variety of techniques, such as the method of logical synthesis, goal setting, goal decomposition, etc. Findings: The implementation of the demoeconomics concept, based on the demoethics values in the context of “spirituality and morality”, “rationality”, “responsibility”, “justice” and “security” contributes to the effective provision of rational use of water resources and basic needs of the population. The results of the Concept are aimed at achieving ethical rationality. Harmonizing with the Sustainable Development Goals (SDG), they not only promote economic growth and meet the needs of society, but also create the preconditions for reducing socio-economic inequality, increasing economic responsibility and respect for cultural and spiritual values. Conclusions: The sustainability of ethical rationality requires the transformation of the values of members of society when using natural resources based on the concept of demo-economics, based on the values of demo-ethics in the context of “spirituality and morality”, “responsibility”, “justice”, “rationality” and “security”, which can provide a balance between economic, social and environmental needs of humanity, to the manifestation of moral behavior in any life situation, contributing to the sustainability of the quality of life of members of society and the competitiveness of the region.